Screening of Rhizobacteria for Plant Growth Promotion and Their Tolerance to Drought Stress - RAHAYU FITRIANI WANGSA PUTRIE; ARIS TRI WAHYUDI; ABDJAD ASIH NAWANGSIH; EDI HUSEN (Indonesian Society for microbiology, 2013)
Rhizobacteria have been known for their capability as plant growth promoter through some mechanisms, directly and indirectly. The purpose of this research to screen rhizobacteria of Bacillus spp. and Pseudomonas spp. for their drought tolerance as plant growth promoter of maize (Zea mays). Screening of rhizobacteria as growth promoter of 47 isolates of Bacillus CR and 34 isolates of Pseudomonas CRB resulted 24 and 9 isolates were able to stimulate the growth of maize sprouts, respectively. Further screening of those growth promoter of the rhizobacterial isolates to drought tolerance resulted 7 isolates of Bacillus CR and 6 isolates of Pseudomonas CRB that were able to grow on medium with osmotic pressure -1 and -2 MPa, respectively. Potential rhizobacterial isolates of growth promoter and drought tolerance were tested for antagonist mechanisms which aims to determine ability to live together in one carrier medium if to be made formulation. Both non antagonist rhizobacterial isolates were evaluated for their potential in producing exopolysaccharide (EPS) revealing that CRB 19 and CR 90 exhibited the highest activity of EPS production up to 0.346 mg mL-1 on medium with -2.0 MPa and 0.107 mg mL-1 on medium with -0.73 MPa, respectively. Based on 16S rRNA sequence analysis, it revealed CRB 19 and CR 90 had highest similarities to Pseudomonas aeruginosa strain B2 and Brevibacillus brevis B33, respectively. Those growth promoter and drought tolerant of Bacillus CR and Pseudomonas CRB had potency to be developed as inoculants in dry land agriculture.